Relational nature of decision-making between patients with advanced illness and caregivers in palliative care: A systematic review and narrative synthesis - Foley, Geraldine; Mockler, David; Walsh, Cathal; Guinan, Emer (My University, 2025)
Background: Clinical practice in palliative care points to the involvement of caregivers in the decision-making process for patient treatment and care. Objectives: The primary objective was to explore the relational nature of decision-making between patients with advanced illness and their caregivers in palliative care. The secondary objective was to identify decision-making styles between patients and their caregivers. Methods: Systematic review and narrative synthesis of empirical research published between January 2004 and September 2024 relevant to the topic was conducted. Databases used included EMBASE, Medline, CINAHL, PsycINFO, Web of Science, and Google Scholar. Results: Thirty-five studies from across 20 countries were included in the review. Multiple factors intertwined with patient and caregiver decision-making processes including patient and caregiver degree of awareness of the patient’s illness, quality of communication (or lack of communication) between each other, caregiving responsibilities, the reciprocation of emotional support between the patient and caregiver, and limitations in service provision. Different approaches to and/or forms of decision-making were identified. These included patients making decisions without involving caregivers, shared decision-making between the patient and caregiver, and preference-based decision-making for both patients and caregivers. Patients and caregivers could avoid disclosure between one another which in some cases, delayed decision-making. Caregivers assumed more control in decision-making when patients became more dependent on them. Conclusions: Mutual disclosure between patients with advanced illness in palliative care and their caregivers could be beneficial to avoid delays in decision-making. Decision-support interventions in palliative care should be designed to both protect patient autonomy and facilitate caregiver support.
PUBLISHED
Keywords: Palliative care; clinical decisions; supportive care; communication; family management